Q. 255.0( 1 Vote )

Mark the correct A. 5

B. 3

C. 10

D. 12

Answer :



p(x=n-1) =


p(x=n-1) = nCn-1 pn-1 q1

Since p=q

p(x=n-1)= n pn-1q

=n pn-1p



comparing LHS anr RHS

we have,


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses

A box has 100 penMathematics - Exemplar

State True or FalMathematics - Exemplar

A random variableMathematics - Board Papers

How many times muMathematics - Board Papers

A card from a pacMathematics - Board Papers

An experiment sucMathematics - Board Papers

A bag A contains Mathematics - Board Papers

On a multiple choMathematics - Board Papers

Mark the correct RD Sharma - Volume 2